2020
DOI: 10.3928/23258160-20200129-10
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented Ocular Fundus Lesions Associated With Familial Adenomatous Polyposis

Abstract: A 36-year-old man was referred for evaluation after trauma to the left eye. He gave a history of familial adenomatous polyposis (FAP) diagnosed at age 15 years and treated with prophylactic colectomy. Funduscopy revealed multifocal pigmented ocular fundus lesions at the level of the retinal pigment epithelium (RPE) in both eyes (Figure 1A and 1B ). The lesions were haphazardly distributed, oval-shaped, variable in size, and with irregular borders. On fundus autofluorescence, the RPE les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Further studies are needed to elucidate this possible association. Interestingly, in the ocular region APC gene mutations have been associated with pigmented ocular fundus lesions [ 18 , 19 ]. Remarkably, previous genetic studies found an association between BFH and PTCH1 gene mutations, which is a gene that normally encodes the patched-1 protein that acts as the receptor for the Sonic Hedgehog (SHH) protein [ 1 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to elucidate this possible association. Interestingly, in the ocular region APC gene mutations have been associated with pigmented ocular fundus lesions [ 18 , 19 ]. Remarkably, previous genetic studies found an association between BFH and PTCH1 gene mutations, which is a gene that normally encodes the patched-1 protein that acts as the receptor for the Sonic Hedgehog (SHH) protein [ 1 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the curative effect of laser treatment alone is gradually reduced with time and is difficult to last, so it is of great significance to explore treatment methods with strong and lasting effect. Studies have found that triamcinolone acetonide, as a glucocorticoid, reduces extracellular fluid exudation and inhibits fibroblast proliferation, thereby controlling and alleviating intraocular inflammation in patients [ 20 – 22 ]. Foreign scholars believe that intravitreous injection of triamcinolone acetonide can maintain a high concentration of the drug in the eye for a long time, which is conducive to the exertion of drug efficacy, effectively inhibit the formation of retinal, choroidal, and iris neovascularization, and also be used to treat macular edema caused by various causes [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of RPEHs in FAP is well documented [12][13][14][15] and has been shown to be present in 60-85% of patients with FAP [3,4]. RPEHs are thought to be congenital, relating to the length of the truncated APC protein product [8].…”
Section: Retinal Pigment Epithelium Hamartomas In Familial Adenomatou...mentioning
confidence: 99%
“…In families with FAP without the ocular trait, negative ophthalmic examination does not indicate absence of the disease. The use of autofluorescence could be helpful in identifying hidden RPEHs [15]. In RPEH-positive families, ophthalmic examination with DNA analysis and endoscopy has been shown to enhance risk assessment in family members who are carriers [31].…”
Section: Case Reportmentioning
confidence: 99%